The effect of ultrasonic treatment on the particle size and specific surface area of LaCoO3 - Sompech S. (Elsevier BV, 2015)
It is well known that the properties of the materials depend on the synthesis process. The controlled synthesis concern particle size and specific surface area of LaCoO3 material is necessary in many applications, such as catalysis and gas sensitivity. Since the activity of a catalysis strongly depends on the particle size and specific surface area. In this study, LaCoO3 powder was synthesized by grinding, heating and washing operations. Firstly, mixture powder of starting materials, LaCl3, CoCl2 and Na2CO3 was ground by using a planetary ball mill grind at speed 300 rpm for 2 h. Secondly, the ground sample was calcined at 600°C for 90 minutes. Finally, the sample product was washed with distilled water under ultrasonic for different treatment times to remove the NaCl phase. The ultrasonic bath was sonicated at a frequency of 40 kHz with a total nominal output power of 95 W for 0, 2, 4 and 6 minutes. All prepared samples were characterized by XRD, particle size analyzer, BET and SEM analysis. XRD patterns clearly showed the complete formation of LaCoO3 with a single-phase of perovskite structure from this synthesis. Moreover, it was found that increasing of the sonication treatment time increases the specific surface area of the prepared samples while decreasing the average particle size D[4,3]. In addition, SEM micrographs also revealed that the morphology is significantly influenced by the sonication time of treatment. © 2010 Published by Elsevier Ltd.